Early life determinants of physical activity in 11 to 12 year olds: cohort study. Issue 7634 (23rd November 2007) - Mattocks, Calum; Ness, Andy; Deere, Kevin; Tilling, Kate; Leary, Sam; Blair, Steven N; Riddoch, Chris
Abstract : Objective To examine factors in early life (up to age 5 years) that are associated with objectively measured physical activity in 11-12 year olds. Design Prospective cohort study. Setting Avon longitudinal study of parents and children, United Kingdom. Participants Children aged 11-12 years from the Avon longitudinal study of parents and children. Main outcome measure Physical activity levels in counts per minute (cpm) and minutes of moderate to vigorous physical activity for seven days measured with a uniaxial actigraph accelerometer. Results Valid actigraph data, defined as at least three days of physical activity for at least 10 hours a day, were collected from 5451 children. Several factors were associated with physical activity at ages 11-12 years. Regression coefficients are compared with the baseline of "none" for categorical variables: maternal brisk walking during pregnancy (regression coefficient 5.0, 95% confidence interval −8.5 to 18.5; cpm for <1 h/wk and ≥2 h/wk of physical activity 17.7, 5.3 to 30.1), maternal swimming during pregnancy (21.5, 10.9 to 32.1 and cpm for <1 h/wk and ≥2 h/wk of physical activity 24.2, 7.8 to 40.7), parents' physical activity when the child was aged 21 months (28.5, 15.2 to 41.8 and cpm of physical activity for either parent active and both parents active 33.5, 17.8 to 49.3), and parity assessed during pregnancy (2.9, −7.6 to 13.4 and cpm of physical activity for 1 and ≥2 parity 21.2, 7.1 to 35.3). Conclusions Few factors in early life predicted later physical activity in 11-12 year olds. Parents' physical activity during pregnancy and early in the child's life showed a modest association with physical activity of the child at age 11-12 years, suggesting that active parents tend to raise active children. Helping parents to increase their physical activity therefore may promote children's activity.